WE ARE ALL TRANSLATORS NOW: CONSTITUTIONAL ANALYSIS AS TRANSLATION - SOLAN, Lawrence M. (Comparative Legilinguistics, 2016)
European courts and legal scholars are accustomed to construing codes that have been in place for long periods of time. In the U.S., most laws are recent enough that the meanings of their words have not changed very much over time. This, however, is not true of the Constitution, which was adopted in the late 18th century. There are debates in the U.S. about how faithful current interpreters of the Constitution should be to the original meaning of the Constitution’s language, and over what it means to be faithful to the original meaning of the Constitution’s language. Should we care about what the original drafters had in mind, or about how the public that voted on the Constitution understood the language? Scholars and judges have turned to old dictionaries for help. Now, however, corpus linguistics has entered the scene, including a new corpus of general 18th century English. In this paper, I will suggest that scholars and judges interested in the meanings of the words as then understood should put themselves in the position of lexicographers writing a bilingual dictionary that translates the terms from a foreign language into contemporary English. Such a stance will bring out the many difficult problems in using a corpus as a means of making legal decisions today.